Institutional and financial assessment of Caribbean Export Development Agency in the context of the Caribbean Trade and Private Sector Development Programme (CTPSD) : final report (ECORYS-NEI RotterdamNL, 2006)
Provides an opinion of the efficiency and effectiveness of the organisation, particularly of its systems of financial management. Provides also, information to facilitate the signing of a Contribution Agreement between CEDA and the European Commission for the second phase of the CTPSD Programme.
Limited circulation